Student History teachers’ personal theories on teaching: Autobiographies and their emerging professional identities (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Philosophy of teaching statements are autobiographical reflective statements on teaching and learning. Such statements can therefore be regarded as a window into the professional identities of teachers, and are increasingly called for internationally when promotion and appointments are considered. In this paper the philosophy of teaching statements of final-year History Education student teachers, are used as the units of analysis. Although meaningful themes on their emerging professional identities as prospective History teachers materialised, in the article I argue that their philosophy of teaching statements were burdened by constraints such as a lack of experience and the educational context they found themselves in. In conclusion I contend that although the philosophy of teaching statements provided nothing more than a porthole into the multilayered emerging professional identities of the History student teachers it gave the latter the opportunity to develop a picture of themselves as History teachers.
Keywords: Philosophy of teaching; Professional identities; Teaching autobiographies; History education; Student history teachers; Theories on teaching